The Dissemination of Development of Economic Potential in the Perspective of Community Empowerment-Based Entrepreneurship in Mosso Village the Papua-PNG Border - Anita Apriani (LPPM Universitas Internasional Batam, 2023)
The economic development in terms of developing regional economic potential has not been implemented evenly. Including in the interior areas of Papua Province, Jayapura City, to be precise, one of the vilages on the border on Indonesia and Papua New Guinea, namely Kampung Mosso. Ignorance or lack of understunding is one of the reasons for the infrequent economic aspect being considered very low because it still depends on central government grants. The method of implementing this community service is to conduct outreach regarding the potential that can be formed and developed into several ongoing economics activities and to form an entrepreneurial spirit in the Mosso Village community. The goals and expectations of the implementation of this community service activity are so that the community is able to have a useful role in developing the regional economy towards a prosperous area independently.